Atypical Antibody Dynamics During Human Coronavirus HKU1 Infections - Sechan, Ferdyansyah; Grobben, Marloes; Edridge, Arthur W. D.; Jebbink, Maarten F.; Loens, Katherine; Ieven, Margareta; Goossens, Herman; van Hemert-Glaubitz, Susan; van Gils, Marit J.; van der Hoek, Lia (Frontiers in Microbiology, 2022)
Human coronavirus HKU1 (HCoV-HKU1) is one of the four endemic coronaviruses. It has been suggested that there is a difference in incidence, with PCR-confirmed HCoV-NL63 and HCoV-OC43 infections occurring most, and HCoV-HKU1 the least. Lower incidence of HCoV-HKU1 infection has also been observed in serology studies. The aim of the current study was to investigate antibody dynamics during PCR-confirmed HCoV-HKU1 infections using serum collected during infection and one month later. We expressed a new HCoV-HKU1 antigen consisting of both the linker and carboxy-terminal domain of the viral nucleocapsid protein, and implemented it in ELISA. We also applied a spike-based Luminex assay on serum samples from PCR-confirmed infections by the four endemic HCoVs. At least half of HCoV-HKU1-infected subjects consistently showed no antibody rise via either assay, and some subjects even exhibited substantial antibody decline. Investigation of self-reported symptoms revealed that HCoV-HKU1-infected subjects rated their illness milder than subjects infected by other HCoVs. In conclusion, HCoV-HKU1 infections reported here displayed atypical antibody dynamics and milder symptoms when compared to the other endemic HCoVs.